Writing for science and engineering papers, presentations and reports - Silyn-Roberts, Heather (London ; Waltham, MA : Elsevier, 2013)
"In this fully updated and revised edition, Dr. Silyn-Roberts explains in plain English the steps to writing abstracts, theses, journal papers, funding bids, literature reviews, and more. The book also examines preparing seminar and conference presentations. Written in a practical and easy to follow style specifically for postgraduate students in Engineering and Sciences, this book is essential in learning how to create powerful documents"--Publisher's website.
Document structure : the requirements for each section -- Specific types of documents -- Referencing, editorial conventions, revising, proofreading -- Writing style -- Presenting your work orally.
Keywords: Technical writing -- Handbooks, manuals, etc; Communication in science; Communication in engineering; Communication of technical information